경도인지장애와 경도치매 단계에서의 한의 변증 및 간 혈액지표 연관성 탐색 연구 - 김가혜; Kahye Kim; 차지윤; Jiyun Cha; 김슬기; Seul Gee Kim; 강형원; Hyung-won Kang; 유영수; Yeoung-su Lyu; 정인철; In Chul Jung; et al. (동의신경정신과학회지, 2023)
Objectives: This study aimed to comprehend the characteristics of Korean medicine patterns in relation to varying degrees of cognitive impairment in an elderly population. Methods: The dataset included 127 elderly individuals with cognitive impairment obtained from three Korean medicine hospitals between 2018 and 2021. The participants were categorized into two groups based on Clinical Dementia Rating-Sum of Boxes (CDR-SB) scores: those with questionable impairment (QI) and those with very mild dementia (VMD). A diagnostic framework for Korean medicine patterns encompassing Qi deficiency, Yin deficiency, Phlegm dampness, and Heat-fire was employed. Liver blood markers, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), and the AST/ALT ratio, were also analyzed. Results: The scores of the cognitive assessment tools (MoCA-K, MMSE-DS, and K-IADL) of the QI group significantly differed from those of the VMD group. CDR-SB exhibited a positive correlation with the scores of each pattern of Qi deficiency, Yin deficiency, Phlegm dampness, and Heat-fire, whereas ALT and AST values displayed negative correlations. Binomial logistic analysis, controlling for potential confounders, such as age, education years, body mass index, the presence of chronic disease, and the presence of medication, verified that the VMD group showed higher pattern scores and lower ALT and AST values than the QI group. Conclusions: Increases in pattern scores along with decreased AST and ALT levels might be indicative of more severe cognitive impairment.